Genetic variants in the glutathione S-transferase genes and survival in colorectal cancer patients after chemotherapy and differences according to treatment with oxaliplatin - Kap, Elisabeth Johanna; Rudolph, Anja; Jansen, Lina; Ulrich, Alexis; Hoffmeister, Michael; Ulrich, Cornelia; Brenner, Hermann; Chang-Claude, Jenny (Pharmacogenetics and genomics, 2014)
Introduction: The glutathione S-transferase (GST) enzymes are involved in the detoxification of a range of carcinogenic compounds as well as chemotherapeutic agents. Therefore, genetic variants in the GST genes could influence survival in patients with colorectal cancer (CRC). Results from previous studies have been inconsistent and therefore we investigated the association between the GSTP1 ile105val polymorphism and the copy number variants of the GSTM1 and GSTT1 genes and survival in CRC patients treated with adjuvant/palliative chemotherapy. Patients and methods: We included 755 CRC patients with stage II-IV disease from two population-based studies carried out in Germany. Genotyping of the GSTP1 polymorphism was carried out using fluorescence-based melting curve analysis and copy number variants were determined using a multiplex PCR. Survival analysis was carried out using the Cox regression model, adjusting for age, sex, UICC stage, cancer site, and radiation therapy. Results: Compared with noncarriers, CRC patients who were homozygote carriers of GSTM1 had significantly poorer survival after treatment with oxaliplatin [hazard ratio (HR) 2.25, 95% confidence interval (CI) 0.93-5.44] than those not treated with oxaliplatin (HR 0.64, 95% CI 0.30-1.34; P for heterogeneity=0.031). The association was significant in metastatic CRC patients treated with oxaliplatin (HR 3.59, 95% CI 1.29-10.03). Neither the GSTP1 105val allele nor the GSTT1 deletion was significantly associated with CRC survival. Conclusion: Our data suggest that GSTM1 may be a predictive marker for oxaliplatin therapy; however, independent large studies are warranted to confirm these results.
Gesehen am 30.09.2020